Pendampingan Strategi Promosi Media Sosial pada UMKM Krecek Rambak “UD Rengas Jaya” Mojoanyar Kabupaten Mojokerto - M.Syamsul Hidayat; Budi Utami; Eny Setyariningsih; Toto Heru Dwihandoko (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Social media is one of the main digital marketing strategies used to promote business products, with the aim of obtaining maximum profits (Hidayat et al., 2022). Social media and digital technology are gradually changing the way companies market their own products (Fraccastoro et al., 2021). However, there are still many MSMEs that do not use online sales optimally when marketing their products. Likewise, the MSME